Advancing the entrepreneurial orientation construct: the role of passion and perseverance. Issue 4 (7th November 2016) - Gerschewski, Stephan; Lindsay, Valerie J.; Rose, Elizabeth
Abstract : Purpose: The purpose of this paper is to examine how entrepreneurial orientation (EO) is manifested in the context of born global firms. Specifically, the authors investigate the extent to which the EO dimensions of the influential Miller/Covin & Slevin scale are demonstrated in born globals. In addition, following calls in the literature, some as-yet unrecognised dimensions of EO in born globals are examined. Design/methodology/approach: The authors use a qualitative research approach by conducting semi-structured, in-depth interviews with eight born global firms from New Zealand and Australia. Findings: The authors find that the EO dimensions of proactiveness and innovativeness are strongly prevalent in these firms. In contrast to the extant literature, the results also indicate that these born global firms generally display a relatively low level of risk-taking. The authors find strong empirical support for two additional emerging dimensions of EO: passion and perseverance. Originality/value: The study provides two key contributions to the area of international entrepreneurship by investigating how EO is prevalent in the context of born globals and by proposing the new dimensions of passion and perseverance.